Model Perkuliahan Microteaching Berbasis RME untuk Meningkatkan TPACK Mahasiswa Calon Guru - Irianti, Nathasa Pramudita; Rozhana, Kardiana Metha (JMPM: Jurnal Matematika dan Pendidikan Matematika, 2024)
This research aims to develop an RME-based lecture model for Microteaching courses that can increase the Technological, Pedagogical, and Content Knowledge (TPACK) of prospective teacher students. The lecture model developed is a learning tool that is implemented in the Microteaching course in the Mathematics Education Study Program. The development of this lecture model uses the modified 4-D Development Model introduced by Thiagarajan, Semmel & Semmel. The 4-D model consists of four stages, namely define, design, develop, and disseminate. The development product is in the form of lecture tools consisting of lesson plans, and evaluation assessments whose validation has been tested by two experts in the field of learning tools and learning media. In addition, trials were carried out on prospective teacher students who took the Microteaching course in the 2022/2023 Short Semester. The results of validation tests and trials show that this RME-based lecture model can be implemented to increase the Technological, Pedagogical, and Content Knowledge (TPACK) of prospective teacher students.